Citizen participation in disaster recovery projects and programmes in rural communities: a comparison of the Haiti earthquake and Hurricane Katrina. Issue 3 (27th October 2017) - Pyles, Loretta; Svistova, Juliana; Ahn, Suran; Birkland, Tom
Abstract : This study investigates predictors of local participation in recovery projects and programmes following Hurricane Katrina in the United States in 2005 and the earthquake in Haiti in 2010. Using two sets of survey data, it examines whether disaster impacts and social capital (social trust and civic engagement) are associated with disaster recovery participation and compares predictors of such engagement in the two locations. Multivariate logistic regression results reveal that physical injuries, limited community mobility, and government trust increase recovery participation in Haiti (n=278), whereas emotional distress and homeownership decrease it. On the Gulf Coast of the US (n=259), physical injuries and higher civic engagement augment recovery participation, while homeownership and age reduce it. The confounding factors of national contexts and post‐disaster time frames might explain the differences in the results. The discussion addresses the relation between country‐specific vulnerability and recovery participation and suggests implications for policy and practice to improve local citizens' capabilities to participate in sustainable recovery processes.